The role of high-density lipoproteins in sepsis - Liam R. Brunham (Journal of Lipid Research)
High density lipoproteins (HDLs) are best known for their role in atherosclerotic cardiovascular diseases. However, efforts to reduce cardiovascular risk by increasing the concentration of cholesterol in HDL have failed, raising the question of whether HDL may have other, more central aspects to its role in health and disease. In epidemiological studies, low levels of HDL cholesterol are strongly associated with risk of infectious diseases and death from sepsis and, during sepsis, a larger decline in HDL cholesterol predicts a worse outcome. Many preclinical studies have examined strategies to augment HDL genetically or pharmacologically and have shown that this leads to protection from sepsis in animal models. Data in humans are more limited, but suggest a clinically relevant role of HDL in mediating the response to pathogen-associated lipids and preventing excessive inflammation. Collectively, these data raise the intriguing possibility that a clinically important biological function of HDL is as a component of the innate immune system and suggest that pharmacological manipulation of HDL may be a strategy to reduce the organ dysfunction and death that results from uncontrolled inflammation during sepsis. This review article discusses recent advances in our understanding of the role of HDL in sepsis.